KELAYAKAN LULUR DAUN JAMBU BIJI (PSIDIUM GUAJAVA L) DENGAN PENAMBAHAN BERAS KETAN PUTIH (ORYZA SATIVA GLUTINOSA) UNTUK PERAWATAN KULIT BADAN KERING - Eflina, Husnul; Astuti, Murni (Universitas Negeri Surabaya, 2024)
Nowadays there are many skin problems, especially dry skin such as chapped skin, rough and scaly skin, which can be caused by several environmental factors such as sun exposure, low humidity, skin diseases and the use of bath soap without moisturizers which can triggers dry skin. Seeing the importance of protecting and caring for the skin, skin care can be done by using cosmetics, one of which is body scrub. This research aims to analyze the manufacture of cosmetic scrubs using guava leaves as basic ingredients added with white sticky rice, based on laboratory tests (flavonoids, Vitamin C, and pH), organoleptic tests (texture, color and aroma) hedonic tests (panelists' preferences ). This research uses a quantitative method, with an experimental research design. The data collection techniques used are observation, questionnaire and documentation methods. The independent variable in this study was guava leaf scrub with the addition of white sticky rice. . The dependent variable in this research is the content test contained in guava leaves and white sticky rice, the organoleptic test includes texture, aroma and color, as well as the hedonic test (panelists' preferences) which will be carried out by 5 panelists consisting of 2 Tata lecturers. Makeup and Beauty, Faculty of Tourism and Hospitality, Padang State University, 2 students class of 2019, and 1 person from the Padang Muslimah Beauty Care Industry. The results of this research are 50 grams of guava leaf scrub with the addition of 20 grams of white sticky rice in powder form. Judging from the results of laboratory tests, this scrub has a flavonoid content of 5.5166 ppm/0.5516%, it also contains vitamin C which is good for the skin, namely with a vitamin content of 0.6494% ppm (mg/liter), and has an acidity level (pH) of around 5.8, which is in accordance with beauty standards for body care cosmetics. Based on the organoleptic test results seen from the texture test, it is feasible because in this study 80% of the panelists stated that the scrub had a rough texture. The organoleptic aroma test results are appropriate because in this study 80% of the panelists stated that the body scrub had a strong aroma. The results of the organoleptic color test were very appropriate because in this study 100% of the panelists stated that the body scrub was green. Judging from the panelists' preferences, it was appropriate because in this study 60% of the panelists stated that the panelists liked the guava leaf scrub with the addition of white sticky rice. Keywords: Body Scrub, Guava Leaves, White Glutinous Rice, Dry Body Skin